2017
DOI: 10.3390/w9110871
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Relative Contribution of Dissolved Carbon by the Red River to the Atchafalaya River

Abstract: Abstract:The Atchafalaya River (AR), North America's largest swamp river, annually discharges a large volume of freshwater (nearly 200 km 3 ), delivering~25% of the Mississippi River's (MR) flow and the entire Red River's (RR) flow into the Gulf of Mexico. Studies have reported higher levels of organic carbon in the AR's outlets compared to the MR's outlet, raising questions about local carbon sources. In this study, we investigated dissolved organic carbon (DOC) and dissolved inorganic carbon (DIC) inputs int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This study was conducted in the Lower Mississippi River at Baton Rouge, Louisiana, USA (30 • 26 16.6 N, 91 • 11 31.6 W, Figure 1), approximately 369 river km upstream of the river's outlet to the Gulf of Mexico. The Mississippi is the largest river in North America, draining 3.2 million km 2 of land and discharging approximately 680 km 3 of freshwater into the Gulf annually, in combination with the Atchafalaya River [24]. Due to the vast drainage size and diverse land use, the Mississippi River carries dissolved inorganic and organic carbon (DIC and DOC) from various sources, with an average DIC and DOC flux rate of 12.6 Tg yr −1 and 4.1 Tg yr −1 , respectively, at Baton Rouge during the past three years [25].…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted in the Lower Mississippi River at Baton Rouge, Louisiana, USA (30 • 26 16.6 N, 91 • 11 31.6 W, Figure 1), approximately 369 river km upstream of the river's outlet to the Gulf of Mexico. The Mississippi is the largest river in North America, draining 3.2 million km 2 of land and discharging approximately 680 km 3 of freshwater into the Gulf annually, in combination with the Atchafalaya River [24]. Due to the vast drainage size and diverse land use, the Mississippi River carries dissolved inorganic and organic carbon (DIC and DOC) from various sources, with an average DIC and DOC flux rate of 12.6 Tg yr −1 and 4.1 Tg yr −1 , respectively, at Baton Rouge during the past three years [25].…”
Section: Methodsmentioning
confidence: 99%
“…The focus of this study was on the lowermost Atchafalaya River and its two outlets to the Northern Gulf of Mexico: The ARMC and the artificially bifurcated Wax Lake outlet channel (WLOC) (Figure 1c). The Atchafalaya River is the largest distributary of the Mississippi River, carrying approximately 25% of the Mississippi River water and the total flow of the Red River and discharging a combined flow of about 200 km 3 annually (Xu & DelDuco, 2017). The river begins at the confluence of the Red River and the Mississippi River diversion channel, also known as the Outflow Channel, and travels southward for about 220 km before entering the Gulf of Mexico (Figure 1b).…”
Section: The Lowermost Atchafalaya Rivermentioning
confidence: 99%
“…DIC production is more likely occurring largely in soils and floodplain ecosystems using fresher and more reactive sources of organic material produced within the AR Basin. A recent study indicated the Red River may contribute bioavailable DOC to the AR [71], which may explain some of the labile organic material present. Leaf litter from within the basin may provide further source of less degraded organic carbon for respiration; leaf leachates as well as the breakdown of large organic materials to DOC by bacteria and fungi are major sources of DOC to waters [72][73][74].…”
Section: Dissolved Organic Carbon Dynamicsmentioning
confidence: 99%
“…Leaf litter from within the basin may provide further source of less degraded organic carbon for respiration; leaf leachates as well as the breakdown of large organic materials to DOC by bacteria and fungi are major sources of DOC to waters [72][73][74]. Organic material in the AR are compositionally different from that of the MR, indicating significant leaf litter inputs from its landscape as well as the Red River [29,71]. The timing of leaf litter input within this basin corresponds with the only months where DOC mass loads increased from origin to outlet (August-October).…”
Section: Dissolved Organic Carbon Dynamicsmentioning
confidence: 99%